2020
DOI: 10.15288/jsads.2020.s19.68
|View full text |Cite
|
Sign up to set email alerts
|

A Neurobiological Model of Alcohol Marketing Effects on Underage Drinking

Abstract: Objective: Although an association between exposure to alcohol advertising and underage drinking is well documented, the underlying neurobiological contributions to this association remain largely unexplored. From an epidemiological perspective, identifying the neurobiological plausibility of this exposure–outcome association is a crucial step toward establishing marketing as a contributor to youth drinking and informing public policy interventions to decrease this influence. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 128 publications
0
18
0
Order By: Relevance
“…Causality is most convincingly demonstrated by randomized clinical trials, and there are some examples in the alcohol marketing literature of the use of this “gold-standard” research design to evaluate short-term relationships at the psychological, neurobiological, and behavioral levels of analysis (e.g., Jackson & Bartholow, 2020 ; Courtney et al, 2020 ; Noel et al, 2020 ). However, most of the Bradford Hill criteria apply to results from multiple observational studies, especially when randomized clinical trials are difficult to conduct for practical or ethical reasons (e.g., it would be unethical to assign persons to smoke cigarettes as a test of the smoking–lung cancer association).…”
Section: Does Exposure To Alcohol Marketing Have a Causal Influence Omentioning
confidence: 99%
See 1 more Smart Citation
“…Causality is most convincingly demonstrated by randomized clinical trials, and there are some examples in the alcohol marketing literature of the use of this “gold-standard” research design to evaluate short-term relationships at the psychological, neurobiological, and behavioral levels of analysis (e.g., Jackson & Bartholow, 2020 ; Courtney et al, 2020 ; Noel et al, 2020 ). However, most of the Bradford Hill criteria apply to results from multiple observational studies, especially when randomized clinical trials are difficult to conduct for practical or ethical reasons (e.g., it would be unethical to assign persons to smoke cigarettes as a test of the smoking–lung cancer association).…”
Section: Does Exposure To Alcohol Marketing Have a Causal Influence Omentioning
confidence: 99%
“…One deficiency with this method of summarizing the literature, which the present supplement was designed to correct, is that the research literature had never been organized to address multiple causal criteria in a way that would satisfy both the scientist and the policy maker. The articles in this supplement go beyond the evidence from prior reviews of the alcohol marketing literature and attempt at integration (e.g., Babor et al, 2017 ) by critically evaluating a variety of observational and experimental research of putative mechanisms that covers laboratory-based neurobiological studies ( Courtney et al, 2020 ), psychological studies ( Jackson & Bartholow, 2020 ), and econometric studies ( Saffer, 2020 ).…”
mentioning
confidence: 99%
“…There are many observational studies that address alcohol marketing, its thematic content, and its association with underage drinking. There have also been experimental studies that have investigated different aspects of alcohol marketing exposures, primarily in terms of psychological and neurobiological responses to alcohol-related stimuli or cues ( Courtney et al, 2020 ; Finan et al, 2020 ; Jackson & Bartholow, 2020 ). Our approach to summarizing this literature is organized around the Bradford Hill criteria for causality.…”
Section: Methodsmentioning
confidence: 99%
“…Hill suggested that an exposure–disease association must be plausible; that is, there has to be some hypothesized mechanism of action through which an agent embedded in the exposure exerts a biological influence that results in disease. In this supplement there are three contributions that address plausibility ( Courtney, et al, 2020 ; Henehan et al, 2020 ; Jackson & Bartholow, 2020 ). Psychologists develop, measure, and test psychological models in which exposures affect thoughts and cognitions or attitudes, thereby changing the likelihood that an individual will engage in a behavior.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation